DETECTION OF CERTAIN GENETIC MARKERS OF THE PATHOGENIC FACTORS IN AUTOSTRAINS KLEBSIELLA SPP. IN INFANTS - E. V. Bukharova; S. M. Popkova; E. B. Rakova; Y. P. Dhzioev; E. I. Ivanova; N. M. Shabanova; U. M. Nemchenko (Acta Biomedica Scientifica, 2014)
The article presents the results of detection of genetic determinants of pathogenicity in 44 strains of Klebsiella (Klebsiella pneumoniae, Klebsiella oxytoca), isolated from the intestinal habitat of infants with intestinal dysbiosis. The presence of the uge gene was detected in 92 % of cases in K. oxytoca and in 90 % of K. pneumoniae. Kfu gene was detected twice as frequent (30 %) in K. pneumoniae strains than in K. oxytoca (12,5 %); bfp gene was detected in K. oxytoca 5 times more frequently (25 %) than in K. pneumoniae (5 %), as well as stx 1 - 29,2 % and 15 %, correspondingly. The presence of stx 2 gene wasn't recorded in any of the DNA samples. Registration of investigated determinants in DNA of Klebsiella spp. autostrains which are non-clinical isolates indicates pathogenicity factors circulation among them and therefore the risk of the formation of intestinal dysbiosis in children.